Real Value of Advertising Value Equivalent in Sport Sponsorship - Kot, Sebastian; Kucharski, MichaÅ‚ (International Review of Management and Marketing, 2017)
Conducted examinations were aimed at examining to what degree formal values of the advertising value equivalent (AVE) are ahead of their real value. The reason behind setting the real amount of the AVE is that many sponsoring entities supporting sport treat this factor as the main determinant in evaluation of their sponsoring campaign, even though there are justified doubts about its credibility (Hagyari et al., 2016). During the implementation of studies a thesis was adopted that the official value of the AVE is elevated, and hence distort the process of evaluation of sponsorship. Conducted research involved determining number of visual contacts of respondents with logotypes of chosen sponsors while watching video material with volleyball matches. Research process was based on an eye-tracker. Obtained data was used to determine real values of AVE obtained by each brand. Obtained findings allowed to accept the thesis, as applied innovative test procedure confirmed that real value of the AVE, which had been set, was significantly lower in case of every examined enterprise: differences between the official and real value of the AVE fluctuated from 57% to 96%. Sponsoring enterprises shouldn’t base the evaluation of their sponsorship campaigns on official AVE as obtained data may lead to erroneous conclusions. Keywords: Advertising value equivalent, sports sponsorship, eye-tracker JEL Classifications: M31, O32